Fungsi Legislasi Dewan Perwakilan Rakyat Daerah (DPRD) Dalam Pembentukan Peraturan Daerah di Kabupaten Sikka - Elisabeth Defedra Mbejo Sola; Kotan Y. Stefanus; Hernimus Ratu Udju (Lembaga Pengembangan Kinerja Dosen, 2024)
The legislative body is an institution or council that has the duty and authority to make laws and constitutions in a country. In the general explanation of Law Number 23 of 2014, it is stated that the Regional People's Representative Council, hereinafter abbreviated as DPRD, is a Regional People's Representative Institution which serves as an organizing element of the Regional Government.This research using a qualitative descriptive analysis method, namely by explaining or describing the data obtained by providing logical and correct interpretations in accordance with existing facts and or legal rules that are closely related to this research. So this research is a research that is sourced from primary and secondary data using an empirical juridical approach. Based on the research results, the use of the initiative right of Sikka DPRD members in making local regulations in 2018-2021 is still less than optimal. This can be seen based on data on the number of draft local regulations passed in 2018-2021. The number of local regulations produced by Sikka Regency is 34 (thirty-four) local regulations, including 4 (four) local regulations initiated by the DPRD and 30 local regulations initiated by the Regional Government. DPRD tends to be considered passive in contrast to the Local Government which is more pro-active because the proposal of local regulations (Perda) is more dominated by the regional legislative body than the executive body. The obstacles in the implementation of the legislative function of the DPRD of Sikka Regency are caused by internal factors such as level of education and experience, as well as external factors such as lack of political communication between the DPRD and the Local Government. Based on the results of the study, the author's suggestion is that the proposed local regulations be examined and scrutinized in depth to ensure their legal content and impact on society. The DPRD of Sikka Regency needs to improve the capacity of human resources through training and technical guidance related to the formation of initiative local regulations by involving academics and experts.